Vacation Leave, Work Hours and Wages: New Evidence from Linked Employer-Employee Data - Ali Fakih (Institute for the Study of Labor (IZA), 2014)
This paper provides new evidence on the determinants of vacation leave and its relationship to hours worked and hourly wages by examining the case of Canada. Previous studies from the US, using individual level data, have revealed that annual work hours fall by around 53 hours for each additional week of vacation used. Exploiting a linked employer-employee dataset that allows to control for detailed observed demographic, job, and firm characteristics, we find instead that annual hours of work fall by only 29 hours for each additional week of vacation used. Our findings support the hypothesis that pressure at work may lead employees to use more vacation days, but also causes them to work for longer hours.
Keywords: J22; M52; 330; paid vacation leave; used vacation leave; work hours; wages; linked employer-employee data